2012
DOI: 10.1037/a0026457
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the reliability and construct validity of eating disorder measures in white and black women.

Abstract: Most measures of eating disorder symptoms and risk factors were developed in predominantly White female samples. Yet eating disorders affect individuals of all racial and ethnic backgrounds. Black women appear more vulnerable to certain forms of eating pathology, such as binge eating, and less susceptible to other eating disorder symptoms and risk factors, such as body dissatisfaction, compared with their White peers. Despite concern that extant measures do not adequately assess eating concerns among Black wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 75 publications
2
54
1
Order By: Relevance
“…Our findings also speak to the broader difficulty often encountered when attempting to measure disordered eating in different ethnic groups. Previous research found similar patterns of noninvariance when comparing eating disorder measures across Caucasian and African‐American groups . One study that investigated the factor structure of the Eating Attitudes Test‐26 (EAT‐26) in a Mexican‐American sample found that the factor structure differed from that found in Caucasian samples .…”
Section: Discussionmentioning
confidence: 87%
“…Our findings also speak to the broader difficulty often encountered when attempting to measure disordered eating in different ethnic groups. Previous research found similar patterns of noninvariance when comparing eating disorder measures across Caucasian and African‐American groups . One study that investigated the factor structure of the Eating Attitudes Test‐26 (EAT‐26) in a Mexican‐American sample found that the factor structure differed from that found in Caucasian samples .…”
Section: Discussionmentioning
confidence: 87%
“…Measurement invariance holds when there is no systematic error biased against a certain group (Kline, ); that is, if black and white youth have identical levels of eating pathology, they are equally likely to endorse related items regardless of group membership. Notably, other measures of eating pathology have been found to lack invariance for black and white adults (Kelly et al, ), but to our knowledge there are no data on measures for pediatric samples. Given that eating disturbance typically develops adolescence, but can also manifest during middle childhood (Swanson et al, ), elucidating the measurement invariance of the EDE across races is important in order to reliably and validly identify those with eating pathology.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, this study used self-report measures to assess binge eating and eating self-efficacy; the use of these measures may increase the risk of recall bias, social desirability bias, and errors in selfobservation. Strengths of the study include the use of well-established questionnaires that have been validated among nonwhite samples Kelly et al, 2012).…”
Section: Limitations and Future Researchmentioning
confidence: 99%